2021
DOI: 10.2176/nmc.oa.2020-0374
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pedicle Screw Placement Comparing an Electronic Conductivity Device and a Multi-axis Angiography Unit with C-arm Fluoroscopy in Lumbar Fixation Surgery for Safety

Abstract: The aim of this study was to compare the accuracy, safety, and usefulness of percutaneous pedicle screw (PPS) placement for lumbar fixation using a multi-axis angiography unit (MAU) and an electronic conductivity device (ECD) with a cannulated Jamshidi needle with that using a conventional C-arm. Of 65 cases that underwent lumbar fixation (region between L1-S1) during April 2013 to March 2019, 57 cases that could be followed-up for more than 12 months after the procedure were included. Among them, 31 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In retrospective studies, Allaoui et al ., 31 Yurube et al ., 32 and Kudo et al ., 33 showed the accuracy between 87.7% and 93.6%. Kageyama et al 16 . showed a 98% accuracy in retrospective lumbar surgeries with ECD and multi‐axis angiography unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In retrospective studies, Allaoui et al ., 31 Yurube et al ., 32 and Kudo et al ., 33 showed the accuracy between 87.7% and 93.6%. Kageyama et al 16 . showed a 98% accuracy in retrospective lumbar surgeries with ECD and multi‐axis angiography unit.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective studies, Allaoui et al, 31 Yurube et al, 32 and Kudo et al, 33 showed the accuracy between 87.7% and 93.6%. Kageyama et al 16 showed a 98% accuracy in retrospective lumbar surgeries with ECD and multi-axis angiography unit. For prospective randomized controlled trials, Bai et al, 34 Suess et al, 35 Defino et al, 36 Lebhar et al, 37 and Bhogal et al, 38 documented the accuracy from 85% to 97.4%, and shows that ECD increases pedicle screw accuracy, especially in scoliosis surgeries.…”
Section: Safety and Effectiveness Of The Modified Ecd Withmentioning
confidence: 99%
See 1 more Smart Citation